Derivation of analytical seismic fragility functions for common masonry bridge types: methodology and application to real cases. (October 2016) - Zampieri, Paolo; Zanini, Mariano Angelo; Faleschini, Flora
Abstract: Bridges are, in most cases, the most vulnerable elements in the transportation network during an earthquake; therefore, their seismic vulnerability assessment is necessary for a proper planning of the emergency phase and to define a priority for retrofit interventions. A new simplified approach for the fast evaluation of seismic fragility curves of numerous masonry arch bridge clusters is proposed. The aim of this paper is to propose a quickly procedure to estimate the seismic vulnerability of extended roadway and railway bridge networks in emergency conditions and to optimize the retrofit interventions. This methodology can be applied at regional level for the vulnerability assessment of transportation networks with regard to the specific scenario earthquakes formulated. It would allow us to better manage the phase after the main shock so that it should be possible to rationalise resources for the assessment of bridges, to temporarily close the most vulnerable segments of railway or road network and to maintain the use of the safest ones. Highlights: Seismic fragility curves of common masonry bridges are calculated. The fragility curves are simplified obtained from nonlinear kinematic analysis. The procedure proposed is useful for a simplified seismic risk analysis. Two case studies where the procedure has been applied are reported.